2006
DOI: 10.1182/asheducation-2006.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Positron Emission Tomography (PET) Scanning in Managing Patients with Hodgkin Lymphoma

Abstract: Use of positron emission tomography (PET) or PET/ computed tomography (CT) in Hodgkin lymphoma (HL) continues to expand worldwide. PET is currently widely utilized for response assessment after completion of therapy and, to a lesser extent, for pretreatment staging and assessment of response during therapy (therapy monitoring). In pretreatment staging, PET cannot replace CT or bone marrow biopsy (BMB); however, it can provide complementary information to both CT and BMB, potentially resulting in a modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 39 publications
0
76
0
3
Order By: Relevance
“…22,23 The use of PET-CT response (PERCIST 15 ) to guide ES treatment has so far not been evaluated, whereas it is routinely used for this purpose in Hodgkin disease. 24 Early metastatic relapses after Mel/Bu at sites that were not involved at diagnosis, especially in the patient who received local treatment for metastasis, suggests persistent micrometastatic disease, such as that observed in other tumour types. 25 This finding does not argue in favour of local treatment of metastases, although it has been suggested by others for ES and other sarcoma types (for example, rhabdomyosarcoma).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The use of PET-CT response (PERCIST 15 ) to guide ES treatment has so far not been evaluated, whereas it is routinely used for this purpose in Hodgkin disease. 24 Early metastatic relapses after Mel/Bu at sites that were not involved at diagnosis, especially in the patient who received local treatment for metastasis, suggests persistent micrometastatic disease, such as that observed in other tumour types. 25 This finding does not argue in favour of local treatment of metastases, although it has been suggested by others for ES and other sarcoma types (for example, rhabdomyosarcoma).…”
Section: Discussionmentioning
confidence: 99%
“…Various groups have used care-dose CT without the injection of intravenous iodinated contrast agent for attenuation, correction, or anatomical correlation. Previous studies revealed that 18 F-FDG PET-CT has a higher sensitivity and specificity than CE-CT in the evaluation of HL and high-grade NHL (3,4,(7)(8)(9)(10)(11). Moreover, several studies have suggested that PET imaging with care-dose unenhanced CT alone might be sufficient for staging, therapy monitoring, or follow-up in patients with HL and aggressive NHL, except in special cases (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a significant advantage for the evaluation of lymphoproliferative malignancies, particularly for the detection of lymphomatous involvement in organs and nodes of normal size without any mass. Several studies suggest that the sensitivity and specificity of 18 F-FDG PET-CT for the assessment of nodal and extranodal involvement were higher than those of standard contrast-enhanced CT (CE-CT) (3,4,(7)(8)(9)(10)(11). These benefits make 18 F-FDG PET-CT the standard imaging technique for the initial staging, therapy response evaluation and restaging of patients with lymphoma.…”
mentioning
confidence: 99%
“…Imaging of viable tumour tissue is a brand new modality in oncology. Induction of post-treatment PET negativity is associated with a significantly better prognosis in patients with diffuse large cell lymphoma and Hodgkin's lymphoma 41,42 . A new generation of hybrid PET/CT scanners provides an unprecedented quality of imaging by fusing a morphological CT scan and functional (metabolic) image from a PET detector 43 .…”
Section: Fig 6 Time To Treatment Failure In Fl Patients Treatedmentioning
confidence: 99%